Protective properties of inhibitor-containing composite coatings on a Mg alloy. (January 2016) - Gnedenkov, A.S.; Sinebryukhov, S.L.; Mashtalyar, D.V.; Gnedenkov, S.V.
Highlights: A unique method of self-healing coating formation was applied on Mg alloys. A composite layer contains corrosion inhibitor 8-hydroxyquinoline (8-HQ). Electrochemical properties of the coatings have been investigated in this work. Equivalent electrical circuits were used for experimental impedance data modeling. Inhibitor-containing coating improves protective properties of Mg-alloys. Abstract: The method of the inhibitor-containing coatings formation with self-healing properties on the surface of magnesium alloys has been developed. The obtained experimental results indicate that the protective properties of the samples with inhibitor-containing coating were increased in comparison with the samples without coating and the base coating obtained by plasma electrolytic oxidation method (PEO). Electrochemical parameters of the porous and poreless layers on the surface of the samples have been calculated before and after polarization due to experimental impedance data modeling by means of the equivalent electrical circuits.